Limosilactobacillus reuteri DSM 17938 Inhibition of Biofilm Formation by Prevotella intermedia and Fusobacterium nucleatum Across Salivary pH: An In Vitro Study - Ananda, Nissia; Julia, Vera; Bachtiar, Endang Winiati (European Journal of Dentistry, 2024)
Objectives This study aims to investigate Limosilactobacillus reuteri DSM 17938's antibiofilm effects on Prevotella intermedia and Fusobacterium nucleatum, common causes of alveolar osteitis. It seeks topical alternatives to prevent this condition posttooth extraction. The secondary objective is to assess these effects under different pH conditions (pH 4.5 and pH 7), mimicking oral cavity saliva pH dynamics.Materials and Methods Ethical approval was secured for the saliva collection process involving five healthy adult participants who had undergone wisdom tooth extraction. Saliva samples were diligently collected on the 7th day post-surgery. The unstimulated saliva underwent a series of treatments, including the addition of phenylmethylsulfonyl fluoride (PMSF), pH adjustments, centrifugation, and filtration. The pH levels were re-measured, and subsequent adjustments were made to achieve pH values of 4.5 or 7. Limosilactobacillus reuteri DSM 17938, with a concentration of 1×108 colony-forming units (CFU) per 5 drops, was utilized in the study. Biofilm testing involved incubating saliva samples with varying pH (4.5 or 7) alongside bacterial suspensions (Prevotella intermedia, Fusobacterium nucleatum, or a mixed species). The Interlac suspension was introduced, and plates were anaerobically incubated for 24 hours. Biofilm results were obtained using a spectrometer. The test is conducted in triplicate.Statistical Analysis To scrutinize the impact of pH on biofilm development, the acquired data underwent a two-way ANOVA test in SPSS as part of the statistical analysis. A significance level of p<0.05 was used to determine statistical significance.Results Limosilactobacillus reuteri DSM 17938 significantly reduced biofilm formation across bacterial strains (p = 0.000). Statistical analysis indicated a significant impact of pH on biofilm development (p = 0.000) compared to no saliva samples, with higher formation observed under acidic conditions (pH 4.5). However, the pH levels of 4.5 and 7 did not result in significantly different bacterial biofilm formation (p = 0.529).Conclusion This research highlights Limosilactobacillus reuteri DSM 17938's potency in inhibiting biofilm formation of Prevotella intermedia and Fusobacterium nucleatum. Salivary pH variations significantly influence biofilm development, emphasizing the need to consider pH when assessing probiotic effectiveness. Despite limitations in saliva sample sterilization, this study provides valuable insights into alternative approaches for preventing alveolar osteitis. Further research should explore clinical applications and refine sterilization methods for more accurate results.
Keywords: Limosilactobacillus reuteri; biofilm formation; salivary pH; Prevotella intermedia; Fusobacterium nucleatum; alveolar osteitis